Amniotic Fluid. Creatinine, bilirubin - Gonzáles del Riego B., Manuel (2015)
The amniotic fluid is the medium in which the embryo and fetus are developed and as other liquid media agency, has been the subject of research for many years. In recent times, the study has taken a long boom, either to recognize their biochemical or biophysical and its variations throughout the pregnancy, or to recognize its origin, volume and morphological, physical and chemical characteristics related to the fetus and gestational pathology.